2023
DOI: 10.3390/biom13050785
|View full text |Cite
|
Sign up to set email alerts
|

The SLIT/ROBO Pathway in Liver Fibrosis and Cancer

Abstract: Liver fibrosis is a common outcome of most chronic liver insults/injuries that can develop into an irreversible process of cirrhosis and, eventually, liver cancer. In recent years, there has been significant progress in basic and clinical research on liver cancer, leading to the identification of various signaling pathways involved in tumorigenesis and disease progression. Slit glycoprotein (SLIT)1, SLIT2, and SLIT3 are secreted members of a protein family that accelerate positional interactions between cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“… 50 , 51 , 52 , 53 SPI1 committed macrophage maturation and reprogramming by ROBO signaling pathway ( Figure S7 A). 54 , 55 , 56 XBP1 favored the synthesis and secretion of cholesterol to cause immunosuppression, as well as regulating pro-tumoral macrophages signaled by WNT in cancer ( Figure S7 B). 57 , 58 , 59 The rest of the TFs also presented similar patterns ( Figures S7 C‒S7H).…”
Section: Resultsmentioning
confidence: 99%
“… 50 , 51 , 52 , 53 SPI1 committed macrophage maturation and reprogramming by ROBO signaling pathway ( Figure S7 A). 54 , 55 , 56 XBP1 favored the synthesis and secretion of cholesterol to cause immunosuppression, as well as regulating pro-tumoral macrophages signaled by WNT in cancer ( Figure S7 B). 57 , 58 , 59 The rest of the TFs also presented similar patterns ( Figures S7 C‒S7H).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that distinct tumor cells display varying expression patterns at different stages of tumor angiogenesis, cell invasion, metastasis, and infiltration, in addition to varying levels of SLIT/ROBO signaling. The SLIT and ROBO axon-guidance molecules are now known to perform new functions in the onset of liver fibrosis and cancer [55]. ROBO1 has been implicated as a tumor suppressor for various types of cancer, including breast cancer, and the transmembrane proline-rich γ-carboxyglutamic acid protein 4 (PRRG4) may be a novel target for treating metastatic breast cancer; however, the regulation of ROBO1 expression during tumorigenesis remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…In precancerous intestinal lesions and during tumor progression, Slit2/Robo1 signaling triggers the Wnt/β-catenin pathway by down-regulating E-cadherin and induces EMT [ 61 ]. In HCC, ESCC, PDAC and GC, the Robo1 signaling axis activation can promotes cancer progression, and metastasis [ 63 67 ]. Conversely, deubiquitinating and stabilizing ROBO1 in CRC can inhibit tumor migration [ 68 ].…”
Section: Various Patterns Of the Pns-mediated Regulation On Gi Tumori...mentioning
confidence: 99%